2019
DOI: 10.3892/etm.2019.7552
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑15b participates in the development of peripheral arterial disease by modulating the growth of vascular smooth muscle cells

Abstract: As an atherosclerotic disease, the process of peripheral arterial disease (PAD) is complicated and includes the abnormal proliferation of vascular smooth muscle. The current study aimed to determine the role of microRNA-15b (miR-15b) in the development of PAD and its associated mechanisms. Human vascular smooth muscle cells (hVSMCs) were used in the current study. To assess the effects of miR-15b on hVSMCs, miR-15b was up- or downregulated in hVSMCs using miR-15b mimics or miR-15b inhibitors respectively. Cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
(39 reference statements)
2
8
0
Order By: Relevance
“…In the current study, miR-15b-5p and miR-92b-3p were down-regulated both in the two independent cohorts of OSA patients and in response to IHR stimuli in vitro, and able to counteract oxidative stress-related cell apoptosis. In line with our findings, miR-15b has been shown to inhibit angiogenesis in proliferative diabetic retinopathy via targeting VEGFA, inhibit vascular smooth muscle cells in peripheral artery disease via targeting IGF1R, counteract senescence-associated mitochondrial dysfunction in skin aging via targeting SIRT4, and suppress Th17 Differentiation in multiple sclerosis by targeting O-GlcNAc [ 42 , 43 , 44 , 45 ]. In contrast, miR-15b has been found to augment cell apoptosis in Parkinson’s disease via targeting the GSK-3β/β-catenin signaling pathway, contribute to depression-like behavior in mice by affecting synaptic protein levels and function in the nucleus accumbens, deteriorate cardiomyocyte apoptosis in myocardial infarction via targeting Bcl-2/MAPK3, and contribute to extra-cellular matrix degradation in intervertebral disc degeneration via targeting SMAD3 [ 46 , 47 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the current study, miR-15b-5p and miR-92b-3p were down-regulated both in the two independent cohorts of OSA patients and in response to IHR stimuli in vitro, and able to counteract oxidative stress-related cell apoptosis. In line with our findings, miR-15b has been shown to inhibit angiogenesis in proliferative diabetic retinopathy via targeting VEGFA, inhibit vascular smooth muscle cells in peripheral artery disease via targeting IGF1R, counteract senescence-associated mitochondrial dysfunction in skin aging via targeting SIRT4, and suppress Th17 Differentiation in multiple sclerosis by targeting O-GlcNAc [ 42 , 43 , 44 , 45 ]. In contrast, miR-15b has been found to augment cell apoptosis in Parkinson’s disease via targeting the GSK-3β/β-catenin signaling pathway, contribute to depression-like behavior in mice by affecting synaptic protein levels and function in the nucleus accumbens, deteriorate cardiomyocyte apoptosis in myocardial infarction via targeting Bcl-2/MAPK3, and contribute to extra-cellular matrix degradation in intervertebral disc degeneration via targeting SMAD3 [ 46 , 47 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 87%
“…OSA is independently associated with impaired endothelial function and atherosclerosis through inflammation, oxidative stress, autonomic nervous system activation, and platelet activation [ 40 , 41 ]. Specifically, up-regulations of the miR146b, miR-421, miR-10a, miR-106a, miR-18a, miR-374b, miR-223, and miR-335 genes are implicated in the progression of atherosclerosis, cancer, oxidative stress, ischemic stroke, or insulin resistance, while down-regulations of the miR-150, miR-29c, miR-133a, and miR-145 genes are implicated in protection from heart failure, cancer, or insulin resistance [ 6 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study confirmed this hypothesis, demonstrating that miR-15b mimics significantly reduced the viability and facilitated the apoptosis of human VSMCs, and that opposite effects were observed following miR-15b inhibitor transfection. Further confirmation of this hypothesis was reported in a recent study by Sun et al ( 24 ).…”
Section: Discussionsupporting
confidence: 82%
“…The known downstream target genes of miR-15b-5p include axin 2( 21 ), progestin and adipoQ receptor family member 3( 22 ), heparanase 2( 23 ), and reversion inducing cysteine rich protein with kazal motifs ( 25 ) in cancer cells, and the insulin like growth factor 1 receptor ( 24 ) in human VSMCs. The present study, for the first time, demonstrated that ACSS2 may also be a direct target of miR-15b-5p using the dual-luciferase reporter system.…”
Section: Discussionmentioning
confidence: 99%
“…miR-15b overexpression alleviated ovarian cancer by inhibiting the PI3K/AKT signalling pathway (43). By contrast, miR-15b participates in the development of peripheral arterial disease by inactivating the PI3K/AKT signalling pathway (44). Therefore, it was speculated that the effects of miR-15b in EC may be related to the PI3K/AKT signalling pathway.…”
Section: Discussionmentioning
confidence: 99%